CORPORATE SOCIAL RESPONSIBILITY ALTERNATIVE MODEL: PETERPAN (PERTANIAN TERPADU PASKA LAHAN PERTAMBANGAN) - Radyan Genta Samodra; Luthfie Masyhadi; Kandung Sapto Nugroho; Agus Sjafari (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
The Peterpan Program (Integrated Agriculture Post-Mining Land) is a CSR initiative of PT PLN Indonesia Power UBP Suralaya which aims to utilize ex-mining land into productive land based on sustainable agriculture, livestock, and fisheries. This program integrates waste management (agriculture, livestock, households, and FABA/PLTU Ash), soil fertility restoration, and community business development. Cilegon City faces challenges in post-mining land utilization, food security needs, and environmental pressures due to energy industry activities. The Peterpan Program is presented as an innovative solution with a community development model that prioritizes community participation, waste utilization, and environmentally friendly cultivation. A community satisfaction survey was conducted to measure the suitability of Peterpan to needs, activeness in planning, implementation, evaluation, local cultural values, social, economic, justice, budget size, utilization of opportunities to express opinions, Indonesia Power commitment, ability to increase knowledge and skills, implementation, dissemination, potential selling value, income, program sustainability and positive benefits of the Peterpan Program. The methodology is structured interviews, field observations, and documentation studies. Respondents: direct and indirect beneficiary communities. The results show that the Community Satisfaction Index (CSI) is 92.5 (Very Good category). The main challenge is maintaining the sustainability of post-mining land amidst climate change, land degradation, and limited community business capital. In conclusion, the Peterpan Program has proven to have a significant socio-economic impact while maintaining environmental sustainability. The excellent satisfaction index indicates strong social legitimacy, but further synergy between actors is needed for this program to be sustainable, expandable, and become a national best practice in post-mining land management. Keywords: Corporate social responsibility; Peterpan; Agriculture; Post-mining land